До 95-річчя Дмитра Васильовича Волкова (1925–1996) - Bakai, O. S.; Bar’yakhtar, V. G.; Gusynin, V. P.; Zheltukhin, O. O.; Zagorodny, A. G.; Loktev, V. M.; Peletminskii, S. V.; Sitenko, Yu. O.; Slyusarenko, Yu. V.; Storizhko, V. Yu.; Uvarov, D. V.; Shulga, M. F. (Publishing house "Academperiodika", 2020)
-